Self-rated health implications of noise for open-plan office workers: An overview of the literature. Issue 2 (June 2023) - Felipe Contin de Oliveira, Sofia; Aletta, Francesco; Kang, Jian
In open-plan offices (OPO), workspaces without ground-to-ceiling dividers, noise is one of the most complained about aspects, causing physical and psychological impacts. With the increasing interest for a human-centric design, notably after the publication of ISO 22955, this review aims to identify the main noise sources in this office layout and the employees' perception of related health effects, evaluating the interventions proposed to overcome their impacts. Following the PRISMA guidelines, a review was conducted using the Scopus and PubMed databases, considering subjective questionnaires distributed in offices, which could include physical workspace assessment. It excluded studies limited to: (a) laboratory experiments; (b) isolated cognitive tests; (c) office layouts other than OPO; (d) systematic reviews; and (e) mathematical models. Sixty studies were identified and the screening process resulted in 11 selected for inclusion, which indicated irrelevant speech, chatting, and telephone ringing as the main noise sources causing productivity loss, stress, and low comfort rates due to distraction and lack of privacy. To overcome these impacts, researchers suggested the use of sound-absorbing surfaces, separated zones for different tasks and headphones, although their effectiveness relies on human behaviour and economic feasibility. Thus, the evidence indicates that noise is a recurrent issue in OPOs, it demonstrates the importance of appropriate acoustic performance of the workspace and the necessity of new studies regarding OPO workers' perception of noise and their health, particularly after the COVID-19 new safety guidelines.